Feeder cattle price differentials: how much did they change over time? - J. Mintert; F. Brazle; J. III Sartwelle; R. Jr. Bolze; Michael R. Langemeier; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1995)
Results from mathematical models of feeder cattle price/characteristics using data collected in Kansa s and Missouri in 1986/1987 and from 1993 using the same data collection and modeling procedures indicate that the implicit values of many feeder cattle characteristics changed over time. Characteristic values often changed whether their value was measured in dollars per hundredweight or as a percentage of the mean feeder p rice during the data collection period. Directional impacts of characteristics on feeder cattle price were generally consistent from 1986/1987 to 1993. These results imply that, as market conditions change, new feeder cattle price/characteristic relationships need to be estimated.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Feeder cattle; Prices; Physical characteristics